Caracterização estrutural da forma recombinante da proteína Pb27 de Paracoccidioides brasiliensis - Juliana Barbosa Coitinho (2009)
COITINHO, J. B. Structural characterization of recombinant form of theprotein Pb27 from Paracoccidioides brasiliensis. 2009. Dissertation(Masters). Departamento de Bioquímica e Imunologia. Universidade Federal de Minas Gerais. Belo Horizonte, 2009. Paracoccidiodomycosis (PCM) is one of the most important systemic mycoses in Brazil. The etiologic agent of the disease is the thermal dimorphic fungusParacoccidioides brasiliensis. The infection causes lesions in the lungs and can disseminate to other organs and tissues. So far, there is no specific control program, standardized diagnostic or treatment protocol for this disease. The recombinant 27-kDa antigen (Pb27r) has been used with high sensibility and specificity in the diagnosis of PCM but its biological function in the fungus is unknown. Besides, no other similar protein has been described so far in databases. The gene of Pb27 was initially cloned in our laboratory into the expression vector pGEX with a GST-tag, but the attempts to crystallize the purified protein were unsuccessful and different constructs have been prepared. The gene was subcloned into the expression vector pET-DEST42 with a His-tagat the C-terminus. Pb27r-CHis was expressed in E. coli BL21 and purified using a metal-affinity chromatography. To confirm the Pb27r expression, a Western blot using mouse anti-Pb27 serum was performed. Crystallization of Pb27r-CHis was initially performed with commercially available sparse-matrix screens using the hanging-drop vapour diffusion technique. So far, no protein crystals have been observed and others 544 conditions were tested automatically, but nocrystals were formed again. In the mean time, the Pb27 gene was alsosubcloned into another expression vector (pDEST 17) with an N-terminal Histag (Pb27r-NHis). This protein was expressed and purified using the same protocol for Pb27r-CHis but the initial crystallization attempts did not produce crystals. The results of the experiments of dynamic light scattering (DLS) and circular dichroism (CD) showed that the proteins, although partially polydisperses in solution, were structured, with about 40% of -helix. In an attempt to facilitate the formation of crystals by minimizing the entropy of the Pb27r surface, site directed mutation was held to exchange two theoretically surface residues, E and K for two A. This protein (Pb27r-mut) was cloned in the vector pDEST 17 but became insoluble. To remove more flexible protein regions that hinder the formation of crystals, the proteins Pb27r-CHis and Pb27r-NHis were subjected to limited proteolysis with trypsin. A region of approximately 25 kDa remained constant in the two constructs when analyzed by SDS-PAGE and MALDI-MS. As so far, all attempts to crystallize therecombinant Pb27 failed, the crystallization of the native protein through its affinity purification by using anti-Pb27 antibodies obtained from theimmunization of rabbits will be performed. The study of the three-dimensional structure of this protein will enable a more detailed understanding of this molecule, such as the location of their epitopes and its folding. Besides, structural information about this protein could probably help to identify its biological function on P. brasiliensis.